Exposure of Induced Pluripotent Stem Cell-Derived Vascular Endothelial and Smooth Muscle Cells in Coculture to Hemodynamics Induces Primary Vascular Cell-Like Phenotypes. (19th June 2017) - Collado, Maria S.; Cole, Banumathi K.; Figler, Robert A.; Lawson, Mark; Manka, David; Simmers, Michael B.; Hoang, Steve; Serrano, Felipe; Blackman, Brett R.; Sinha, Sanjay; Wamhoff, Brian R.
Abstract: Human induced pluripotent stem cells (iPSCs) can be differentiated into vascular endothelial (iEC) and smooth muscle (iSMC) cells. However, because iECs and iSMCs are not derived from an intact blood vessel, they represent an immature phenotype. Hemodynamics and heterotypic cell:cell communication play important roles in vascular cell phenotypic modulation. Here we tested the hypothesis that hemodynamic exposure of iECs in coculture with iSMCs induces an in vivo-like phenotype. iECs and iSMCs were cocultured under vascular region-specific blood flow hemodynamics, and compared to hemodynamic cocultures of blood vessel-derived endothelial (pEC) and smooth muscle (pSMC) cells. Hemodynamic flow-induced gene expression positively correlated between pECs and iECs as well as pSMCs and iSMCs. While endothelial nitric oxide synthase 3 protein was lower in iECs than pECs, iECs were functionally mature as seen by acetylated-low-density lipoprotein (LDL) uptake. SMC contractile protein markers were also positively correlated between pSMCs and iSMCs. Exposure of iECs and pECs to atheroprone hemodynamics with oxidized-LDL induced an inflammatory response in both. Dysfunction of the transforming growth factor β (TGFβ) pathway is seen in several vascular diseases, and iECs and iSMCs exhibited a transcriptomic prolife similar to pECs and pSMCs, respectively, in their responses to LY2109761-mediated transforming growth factor β receptor I/II (TGFβRI/II) inhibition. Although there are differences between ECs and SMCs derived from iPSCs versus blood vessels, hemodynamic coculture restores a high degree of similarity in their responses to pathological stimuli associated with vascular diseases. Thus, iPSC-derived vascular cells exposed to hemodynamics may provide a viable system for modeling rare vascular diseases and testing new therapeutic approaches. Stem Cells Translational Medicine 2017;6:1673–1683 Abstract : Human induced pluripotent stem cells differentiated into vascular endothelial (iECs) and smooth muscle (iSMCs) cells were cocultured to preserve heterotypic cell:cell communication and exposed to relevant physiological hemodynamics. This application restores a more in vivo-like phenotype of these cell types.